Histomorphological Spectrum and Diagnostic Challenges in Thymic Epithelial Neoplasms with their Prognostic Significance: A Case Series of 33 Cases at a Regional Cancer Center in Western India - Dhandapani, Karthik; Gandhi, Jahnavi; Timaniya, Sonali; Joshi, Krutika; Gami, Amisha; Shah, Ashini; Trivedi, Priti (South Asian Journal of Cancer, 2022)
Objective Pathological diagnosis of thymic epithelial neoplasms is challenging due to multiple subtypes, tumor heterogeneity, and variations in inter-observer reproducibility. Very few studies are available on their spectrum in the Indian subcontinent. In this study, we aimed to explore the morphological spectrum and diagnostic difficulties in the classification and subtyping of thymic epithelial neoplasms along with their prognostic significance in the Indian population.Material and Methods Retrospectively, all surgically resected thymectomy specimens operated at our institute as well as outside review cases during the period were included. Histomorphology and immunohistochemistry (IHC) slides were reviewed and correlated with clinicopathological variables.Statistical Analysis Microsoft Excel 2019 and SPSS version 20 were used for data analysis.Results Among the 33 thymic epithelial neoplasms operated during the study period, the commonest subtype was thymoma B2 type followed by AB, B1, A, and B3 types. A single case each of micronodular thymoma, microscopic thymoma, and thymic carcinoma were identified. Six cases of thymomas with more than one pattern (other than ‘A’) were noted. The male:female ratio was 2:1. Stage I in Modified Masaoka staging and pT1a in TNM staging were most common. Seven cases had metastasis, four during initial presentation and three during subsequent follow-up.Discussion and Conclusion Thymic epithelial neoplasms show morphological overlapping of features. Thorough sampling, morphology, and IHC for exact subtyping of thymoma and diligent search and documenting of lymphovascular invasion (LVI) are vital as both are separate risk factors for metastasis/recurrence and help the clinician in a better follow-up of patients.
Keywords: thymic epithelial neoplasm; thymoma; histomorphology; immunohistochemistry; metastasis